IMPLIKASI MANAJEMEN LABA TERHADAP KONVERGENSI IFRS (INTERNATIONAL FINANCIAL REPORTING STANDARDS) DI INDONESIA - Media Kusumawardani (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2017)
This paper addresses the question whether International Financial Reporting Standards (IFRS) is associated with lower earnings management. The objective of this study is to examine the effect of IFRS convergence on the earnings management of Indonesian firms by using audit quality as moderating variable. The research also includes several control variables (size, leverage, operating cash flow). The research objects were the manufacturing companies listed in Indonesia Stock Exchange from 2010-2013. The method of data collection is random sampling method and resulted 312 firms observation. Type of data are secondary data in the form of financial statement as the media manufacturing companies. The data were analyzed by using multiple regression analysis with Eviews8. In this research, the IFRS convergence is found not to have significant effect on earnings management and the IFRS convergence with audit quality as moderating variable is found not to have significant effect on earnings management. The other result indicates that among the three control variables, size leverage and operating cash flow indicate the negative effect on earnings management. This research indicate that mandatory adopters of IFRS in Indonesia cannot be associated with lower earnings management.